Level of Physical Activity of the Students at the University of Tuzla According to IPAQ - Ivana Ćosić Mulahasanović; Amra Nožinović Mujanović; Edin Mujanović; Almir Atiković (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2018)
The study was conducted using the long version of the International Physical Activity Questionnaire (IPAQ) and the aim of this research is to determine the level of physical activity and differences among students, of the University of Tuzla, in relation to gender. The study was conducted on a sample of 813 students (321 male and 492 female) 1st cycle of studies at the University of Tuzla. The results of present study showed that average level of total physical activity for male students was 6013.493 MET-minutes/week, while female students showed average level of total physical activity was 4619.381 MET-minutes/week. We conclude that the total data indicates that in this group of students the physical activity level is sufficient and that there is a lower physical activity among females than males. Also there is a need to continuously take measures for promoting the sports at Universities with the aim of raising the health status of students to a higher level.